2021
DOI: 10.3126/janr.v4i2.33844
|View full text |Cite
|
Sign up to set email alerts
|

Economics of production and marketing of wheat in Rupandehi district of Nepal

Abstract: Wheat is the third most important cereal crop of Nepal after rice and maize in terms of area. The study on profitability and marketing of wheat was conducted in the Rupandehi district in 2019. The household survey, focus group discussion, interview with the individual market actors such as input suppliers, producers, collectors, wholesalers, millers, and retailers in selected clusters was carried out. The study showed that the Benefit-Cost Ratio of wheat production (BCR) was 1.87. The marketing margins at thre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 11 publications
1
9
1
Order By: Relevance
“…54.46, respectively. Contrary to the findings reported by Kharel et al (2021), where labor costs accounted for the highest proportion of total production costs for wheat, our study identified chemical fertilizer costs as the major contributor to production costs. Notably, chemical fertilizers emerged as the major cost contributor to wheat production.…”
Section: Cost Of Production Of Wheatcontrasting
confidence: 99%
See 1 more Smart Citation
“…54.46, respectively. Contrary to the findings reported by Kharel et al (2021), where labor costs accounted for the highest proportion of total production costs for wheat, our study identified chemical fertilizer costs as the major contributor to production costs. Notably, chemical fertilizers emerged as the major cost contributor to wheat production.…”
Section: Cost Of Production Of Wheatcontrasting
confidence: 99%
“…Similarly, Dhital (2017) reported an overall BCR of 1.22 for wheat production in Nepal. In the Rupendahi region, Kharel et al (2021) found a significantly higher BCR of 1.87, indicating a favorable economic outlook for wheat production in this particular area. This comprehensive analysis provides valuable insights into the economic viability of wheat cultivation in the study area, providing a clear picture of the costs and returns associated with this agricultural enterprise.…”
Section: Benefit-cost Ratiomentioning
confidence: 88%
“…Financial issues being the least severe, this shows that farmers have enough savings for capital investment. Though finance was not the limiting factor for the farmers in Dhangadhi to move forward with the commercial production of vegetables, various authors have identified financial limitation as the number one bottleneck of commercial farming, followed by inadequate market infrastructures such as market information systems, storage facilities, stable market price, and quality assurance services along with technical support services (Joshi and Piya, 2021;Kharel et al, 2021).…”
Section: Ranking Of Problems With Vegetable Productionmentioning
confidence: 99%
“…However, the yield potential has not been fully met as evidenced by a yield gap of 3.0 ton/ha in wheat between research and farmers' field (Basukala and Rasche, 2022). Furthermore, the current yield is well below than the neighboring countries; India (3.37 ton/ha) and China (5.48 ton/ha) (Kharel et al, 2021;Ramadas et al, 2019). Also, the wheat cultivated area is on a decreasing trend (Figure 1).…”
Section: Introductionmentioning
confidence: 99%